Towards a Modelling Process for Simulating Socio-ecosystems with a Focus on Climate Change Adaptation - Federico Cornacchia; Alberto Gabino Martínez-Hernández; Marco Bidoia; Carlo Giupponi (Fondazione Eni Enrico Mattei (FEEM), 2023)
As the impacts of climate change are expected to be increasingly disruptive, a growing share of the economic literature moved to modelling approaches to address the interconnectedness of social, economic, and environmental issues. Among them, System Dynamics (SD) stands out as a well-established modelling approach to analyse complex social-ecological systems. In order to benefit from such modelling exercises it is necessary to follow a structured process, bearing in mind that models should have as their ultimate ambition that of supporting decision-making processes. Yet, the connection with decision-making is addressed only in the last phases of the modelling process, with emphasis placed only on few particular sectors. Hence, a lack of a general framework that can be used as a reference to address climate change adaptation and which could provide insights to economic valuations to support decision-making processes for a different range of sectors emerges. Consistently, the present study aims to bridge the observed gap by employing a combined SES-DAPSIR framework to build a conceptual modelling process for simulating the behaviour of a generic socio-ecosystem, with a particular focus on climate change adaptation. It also illustrates how the proposed conceptual modelling process is concretely put into practice with an application for a coastal socio-ecosystem. This allows demonstrating how the proposed methodology constitute a potential common starting point for different targeted modelling exercises, resulting particularly useful when moving from analytical modelling to decision support.
Keywords: C63; Q54; Q57; 330; Climate change adaptation; system dynamics; decision-making; socio-ecosystem; SES-DAPSIR framework; conceptual modelling